Español - Rojas Pérez, Lino Arturo (2022)
Introduction. Pelvic inflammatory disease refers to infection of the organs of the upper genital tract that involves the uterus, fallopian tubes, ovaries and can affect other pelvic organs, it is generally polymicrobial. Objectives. Determine according to the evidence found the most appropriate management. Methodology. In the search for information, the PICO format was used as a clinical question, and information was obtained from virtual scientific libraries such as Cochrane, EBSCO, Pub Med, ACCESSSS, Centers for Disease Control and Prevention and UptoDate, DynaMed, as search engines scientific information on the management of pelvic inflammatory disease. Results. 35 scientific articles have been found that support the information presented and that meet the criteria proposed in the investigative process. Discussion. Pelvic inflammatory disease is a polymicrobial infection of the upper genital tract, it can cause pelvic peritonitis, infertility problems, chronic pelvic pain, among others, therefore its prevention, timely diagnosis and the best scientific treatment are essential. Conclusions. The use of protocols for the prevention, diagnosis and timely treatment of pelvic inflammatory disease reduces the probable complications that may occur.